2018
DOI: 10.21315/apjee2017.32.2
|View full text |Cite
|
Sign up to set email alerts
|

Physics Achievement in Stem Project Based Learning (PjBL): A Gender Study

Abstract: Today's learners will face increasing global competition for college entrance and jobs after graduation. They need to succeed in work, life and citizenship, as well as skills that are necessary for 21st century. Teaching and learning's in the 21st century has to put the emphasis on the 4Cs, collaboration, critical thinking, creativity, and communication in the gender equality environments. Science, Technology, Engineering, and Math (STEM) Project Based Learning (PjBL) provides students to learn 4Cs skills. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As a result, when a friend who is considered smart is not able to solve the problem given, members of the group do not show an effort to work together to solve the problem and tend to ask the teacher directly. This shows that DI does not train students' persistence in learning and tends to spoil students to gain knowledge (Samsudin et al, 2017). The quality of knowledge possessed by students is relatively lacking and is only focused on answering textual test questions.…”
Section: Discussion the Effect Of Project-based Learning (Pjbl) And Direct Instruction (Di) On The Students' Achievementmentioning
confidence: 95%
See 2 more Smart Citations
“…As a result, when a friend who is considered smart is not able to solve the problem given, members of the group do not show an effort to work together to solve the problem and tend to ask the teacher directly. This shows that DI does not train students' persistence in learning and tends to spoil students to gain knowledge (Samsudin et al, 2017). The quality of knowledge possessed by students is relatively lacking and is only focused on answering textual test questions.…”
Section: Discussion the Effect Of Project-based Learning (Pjbl) And Direct Instruction (Di) On The Students' Achievementmentioning
confidence: 95%
“…The ineffectiveness of the DI model is due to its monotonous nature and students are in the capacity as passive learners, meaning students gain knowledge from the material presented by the teacher during classroom learning (Baran et al, 2018;Samsudin et al, 2017). Students just listen to the explanation about the topic from the teacher and they can only recognize the concept without understanding it properly.…”
Section: Discussion the Effect Of Project-based Learning (Pjbl) And Direct Instruction (Di) On The Students' Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it also helps students learn core subject matter and practice collaboration, communication & critical thinking skills [16]. Additionally, according to [17], the implementation of Project Based Learning can further encourage students' problem-solving skills to achieve higher levels of achievement in physics mechanical tests. Study conducted by [18] revealed that 4Cs-based Project-Based Learning model had a significant effect on students' learning independence and reading comprehension skills.…”
Section: Project Based Learning (Pjbl)mentioning
confidence: 99%
“…Directly and indirectly, self-efficacy showed powerful correlations between academic performance and personal adjustment (Jamali et al, 2015;Samsudin et al, 2017). Students who had confidence when entering college performed significantly better during their first year than students who had less confidence (Chemers et al, 2001;Varon, 2015).…”
Section: Introductionmentioning
confidence: 99%